Short Communication: Bird community and it’s conservation implications in Gunung Tunak Nature Park, Lombok, Indonesia - GITO HADIPRAYITNO; AGIL AL IDRUS; I GDE MERTHA; M LIWA ILHAMDI; I WAYAN SUANA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Hadiprayitno G, Al Idrus A, Mertha IG, Ilhamdi ML, Suana IW. 2019. Birds community and it's conservation implications in Gunung Tunak Nature Park, Lombok, Indonesia. Biodiversitas 20: 1753-1757.  Bird community is an important indicator of ecosystem health. A study was conducted in Gunung Tunak Nature Park to analyze the composition of bird species and the abundance and diversity of bird species. Data were collected by survey method from May to August 2017 on three trails. The bird fauna of  Gunung Tunak Nature Park consisted of 32 species belonging to 27 families and 10 orders. The order Passeriformes accounted for the dominant family and species, with an abundance of 61.6%. The species with the highest abundance is Zosterops chloris (13.9%), following by Orthotomus sepium (12.2%), and Streptopelia chinensis (10.4%). While the diversity index was 3.03, indicating that the bird community in Gunung Tunak Nature Park is still well preserved. Five species are of high conservation priority based on protected by Indonesian Law, Endemicity of Wallacea, and the IUCN Red list i.e., Megapodius reinwardt, Pitta elegans, Caloenas nicobarica, Lalage sueurii, and Dicrurus densus.